Morality of the Executive Power. The Charisma of Good Politics and the ‘Fichtean’ Threat in the Modern Institution State - Adolphi, Rainer (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
As a structural problem of the normative dimension of contemporary societies, the article shows that increasing real justice deficits go hand in hand with high political expectations of ‘justice’, while on the other hand the achievements of the law are often no longer sufficiently valued. This has a background in a certain way in which modern moral and political spheres have diverged, for which the theoretical significance can be illustrated with Johann G. Fichte. Fichte had tried to renew once again the Western cultural idea of the political with maximum moralization – and for this very reason ended up having massive gaps in relation to concrete questions of justice. Today’s mental constellation can be described as ‘inverse Fichteanism’. There is a threat of – especially in the institutional state – a general moralization of all correlations, and above all a (moral) general empowerment of politics (absolutizing the executive). This development stands at the end of an erosion that took place during the 20th century, and which was reflected in the great theoretical positions of decisionism and, on the other hand, of legal positivism.